Anisotropic robust Poly(vinyl alcohol) hydrogels inspired by bio-tissue - Qifeng Jin; Suli Xing; Su Ju; Ya Cao; Ke Duan; Li Jin; Yulin Zhang; Yonglyu He; Jinyao Chen; Jianwei Zhang (Materials & Design)
Poly(vinyl alcohol) (PVA) hydrogels have enormous potential for tissue engineering and sensors owing to their biocompatibility, and tailorable mechanical properties. However, developing PVA hydrogels with high strength and toughness remains a significant challenge. In this work, inspired by bio-tissues that possess hierarchical anisotropic structures, a novel strong and tough PVA hydrogel was developed by using directional freeze-casting method and multiple physical bond-forming approach. The tensile strength and toughness of the resulted PVA hydrogel are 3.7 MPa and 3.27 MJ⋅m−3, which are 7.7 times and 9.9 times greater than those of conventional PVA hydrogels produced by freeze-casting method. The excellent mechanical properties of developed PVA hydrogels are attributed to two aspects: 1) the constructed anisotropic aligned pore wall structures played a key role in distributing the stress and thus impede local crack initiation and propagation, and 2) the formation of abundant sacrificial hydrogen bonds which effectively dissipate energy through dynamic breaking and reformation. The research provides a feasible approach to fabricating bioinspired PVA hydrogels with hierarchical architectures and excellent mechanical performances.